Agents and Peer-to-Peer Computing 7th International Workshop, AP2PC 2008, Estoril, Portugal, May 13, 2008 and 8th International Workshop, AP2PC 2009, Budapest, Hungary, May 11, 2009. Revised Selected Papers - Beneventano, Domenico; Despotovic, Zoran; Guerra, Francesco; Joseph, Sam.; Moro, Gianluca; Perreau de Pinninck, Adrian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the thoroughly refereed post-workshop proceedings of the 7th International Workshop on Agents and Peer-to-Peer Computing, AP2PC 2008, held in Estoril, Portugal, in May 2008 and the 8th International Workshop on Agents and Peer-to-Peer Computing, AP2PC 2009, held in Budapest, Hungary, May 2009, co-located with the International Joint Conference on Autonomous Agents and Multi-Agent Systems, AAMAS. The 13 revised full papers presented were carefully reviewed and selected from numerous submissions. The volume is organized in topical sections on social welfare, distributed information sharing, and network organization and efficiency.
Keywords: Artificial intelligence; Computer communication systems; Application software; Information storage and retrieval; Biometrics (Biology).; User interfaces (Computer systems).; Artificial Intelligence; Computer Communication Networks; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Biometrics; User Interfaces and Human Computer Interaction